1999
DOI: 10.1115/1.2826080
|View full text |Cite
|
Sign up to set email alerts
|

The Leidenfrost Point: Experimental Study and Assessment of Existing Models

Abstract: This study presents a detailed and thorough parametric study of the Leidenfrost point (LFP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
192
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(212 citation statements)
references
References 45 publications
(42 reference statements)
16
192
3
1
Order By: Relevance
“…In general, the Leidenfrost state has been found to be governed by surface chemical properties such as surface energy and composition; thermo-physical properties such as density and thermal conductivity; and also topographic characteristics of the surface the liquid is in contact with (liquid/solid interface). Many studies have shown the Leidenfrost point (LFP) for water on polished stainless steel to be between 280 and 320 O C [1]- [7]; such results have been summarized by Bernardin and Mudawar [7]. Additionally, it has been shown that manipulating surface roughness and nanoporosity can lead to increased wettability, which in turn will increase the LFP [8]- [15].…”
Section: Introductionmentioning
confidence: 90%
“…In general, the Leidenfrost state has been found to be governed by surface chemical properties such as surface energy and composition; thermo-physical properties such as density and thermal conductivity; and also topographic characteristics of the surface the liquid is in contact with (liquid/solid interface). Many studies have shown the Leidenfrost point (LFP) for water on polished stainless steel to be between 280 and 320 O C [1]- [7]; such results have been summarized by Bernardin and Mudawar [7]. Additionally, it has been shown that manipulating surface roughness and nanoporosity can lead to increased wettability, which in turn will increase the LFP [8]- [15].…”
Section: Introductionmentioning
confidence: 90%
“…as well as the gravity, the gas pressure, the liquid flow rate, etc. One can find in the articles of Bernardin et al [4][5][6] a complementary bibliographical review on this subject. In fact, previous research works have generally ignored the effects of the gas pressure on the T N Temperature and the available Leidenfrost temperature models have not met reasonable success.…”
Section: Estimation Of T N and T L Temperaturesmentioning
confidence: 99%
“…This interaction of spray with the wall involves different physical phenomena according to the conditions of impact (speed of the droplets, temperature of the wall, roughness of the surface, etc.) and of the pressure of gases in the combustion chamber [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…At higher temperatures, the droplets exhibit the classical Leidenfrost phenomenon 7,8 , where solidliquid contact is absent because of the presence of a thin vapour layer (thickness E10-100 mm) 9 that completely separates the droplet from the heated surface [10][11][12][13] . The reported values of the Leidenfrost temperature on a flat silicon surface ranges from 200 to 390°C 9,[14][15][16][17][18] . Although the majority of the studies on textured surfaces report a relative increase in the Leidenfrost temperature 10,14,[18][19][20][21][22] , a few recent studies reported a significant decrease in the Leidenfrost temperature on microstructured hydrophobic surfaces [23][24][25][26] .…”
mentioning
confidence: 99%
“…The reported values of the Leidenfrost temperature on a flat silicon surface ranges from 200 to 390°C 9,[14][15][16][17][18] . Although the majority of the studies on textured surfaces report a relative increase in the Leidenfrost temperature 10,14,[18][19][20][21][22] , a few recent studies reported a significant decrease in the Leidenfrost temperature on microstructured hydrophobic surfaces [23][24][25][26] . For example, del Cerro et al 23 observed suspended droplets on heated surfaces composed of hydrophobic micropillars and microholes at temperatures 70% lower than the Leidenfrost point on a smooth surface.…”
mentioning
confidence: 99%